INTELECTUAL PROPERTY RIGHTS IN THEORY OF ECONOMICS ANALYSIS OF LAW PERSPECTIVE - Sudarwanto, AL Sentot; Sulistiyono, Adi; Asrori S, M. Hudi; Suryono, Arief; Muryanto, Yudho Taruno; Cahyaningsih, Diana Tantri; Kharisma, Dona Budi (Jurnal Privat Law, 2023)
This article aims to describe the relevance of the protection of intellectual property rights (IPR) in the perspective of the theory of economic analysis of law. The approach used is a historical approach (historical approach) using primary legal materials and secondary legal materials. The data collection technique used is the literature study technique. Based on the research results, it can be concluded that so far the focus of traditional economic analysts has only highlighted that inventors or holders of exclusive IPR are entitled to incentives or rewards for their findings. Apart from that, giving incentives is also to encourage people to make discoveries that are beneficial to human life. However, they did not highlight the high cost of accessing or using their findings. Even the cost of accessing IP exceeds the cost of the production margin of IP itself. In the perspective of the theory of economic analysis of law, the condition of unbalanced margins can cause injustice.